Application of free and immobilized novel bifunctional biocatalyst in biotransformation of recalcitrant lignocellulosic biomass. (December 2021) - Ariaeenejad, Shohreh; Kavousi, Kaveh; Maleki, Morteza; Motamedi, Elaheh; Moosavi-Movahedi, Ali A.; Hosseini Salekdeh, Ghasem
Abstract: Herein, an innovative, green, and practical biocatalyst was developed using conjugation of a novel bifunctional mannanase/xylanase biocatalyst (PersiManXyn1) to the modified cellulose nanocrystals (CNCs). Firstly, PersiManXyn1 was multi-stage in-silico screened from rumen macrobiota, and then cloned, expressed, and purified. Next, CNCs were synthesized from sugar beet pulp using enzymatic and acid hydrolysis processes, and then Fe3 O4 NPs were anchored on their surface to produce magnetic CNCs (MCNCs). This hybrid was modified by dopamine providing DA/MCNCs nano-carrier. The bifunctional PersiManXyn1 demonstrated the superior hydrolysis activity on corn cob compared with the monofunctional xylanase enzyme (PersiXyn2). Moreover, the immobilization of PersiManXyn1 on the nano-carrier resulted in an improvement of the thermal stability, kinetic parameters (Kcat ), and storage stability of the enzyme. Incorporation of the Fe3 O4 NPs on the CNCs made magnetic nano-carrier with high magnetization value (25.8 emu/g) which exhibited rapid response toward the external magnetic fields. Hence, the immobilized biocatalyst could be easily separated from the products by a magnet, and reused up to 8 cycles with maintaining more than 50% of its original activity. The immobilized PersiManXyn1 generated 22.2%, 38.7%, and 35.1% more reducing sugars after 168 h hydrolysis of the sugar beet pulp, coffee waste, and rice straw, respectively, compared to the free enzyme. Based on the results, immobilization of the bifunctional PersiManXyn1 exhibited the superb performance of the enzyme to improve the conversion of the lignocellulosic wastes into high value products and develop the cost-competition biomass operations. Highlights: Bi-functional mannanase/xylanase (PersiManXyn1) was used as novel/efficient biocatalyst. Immobilization on DA/MCNCs nano-carrier doubled the enzyme's activity at 90 °C. Immobilized enzyme displayed higher Kcat and storage stability than free enzyme. Immobilization provided easy separation/reusability (8 cycles with >50% activity) for enzyme. Immobilized enzyme showed an increase (22–35%) in fermentation yield of different biomasses.